The rapid internationalization of as evidenced by journal metrics - Sun Huh (Korean Society of Pediatric Endocrinology, 2017)
PurposeUsing journal metrics, this paper explores whether Annals of Pediatric Endocrinology & Metabolism has internationalized 4 years after changing its language to English only.MethodsFrom the journal's website and the Web of Science Core Collection, the following metrics were counted or calculated: Number of citable articles, countries of authors and editorial board members, total citations, impact factor, countries of citing authors, citing journal titles, and Hirsch index.ResultsFrom 2012 to 2017, 208 articles were citable. The authors had affiliations in 7 countries and the editorial board members in 14 countries. From 2014 to 2017, the total citations each year were 8, 81, 141, and 61; and the impact factors from 2014 to 2016 were calculated as 0.05, 0.987, and 1.165. The citing authors were from 60 countries, among which the United States, China, South Korea, Italy, and Germany were most common. The journal was cited by 215 journal titles. The Hirsch index was 7.ConclusionThese journal metrics showed that the journal achieved international status 4 years after changing the journals' language into English only. The journal's language policy successfully enabled the journal to rebrand as an international journal.